MENELUSURI NADI HERITAGE: EKSPLORASI JEJAK SEJARAH GEDUNG SATE OLEH MAHASISWA PMM4 INBOUND UPI (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2025)
MBKM offers the Pertukaran Mahasiswa Merdeka (PMM) program, which aims to enhance national identity and promote unity through cross-cultural interaction. One of the activities included in PMM is the Modul Nusantara, which allows inbound UPI students to explore the history of the establishment of the Gedung Sate Museum. The PMM 4 Inbound UPI students' exploration of the historical traces of Gedung Sate is not only an academic development project but also a meaningful contribution to the preservation and understanding of Indonesia's cultural heritage. This research employs a qualitative descriptive approach, collecting data through observation, documentation, and literature review. The study's results were supported by references from relevant literature, including books and scientific journal articles. The history of Gedung Sate is explained, particularly regarding the integration of various international architectural elements during the construction process. Gedung Sate is a Dutch colonial architectural heritage that was constructed between 1920 and 1924. It incorporates traditional Indonesian elements and Western construction techniques. The history, various ornaments, and architectural styles of Gedung Sate are important for PMM 4 Inbound UPI students to understand and experience.